Corporate venture capital programs of European electric utilities: Motives, trends, strategies and challenges - Livieratos, Antonios D.; Lepeniotis, Panagiotis (The Electricity journal, 2017)
The forthcoming paradigmatic changes in the energy sector point to innovation as being one of the main drivers of growth for utilities. In search for their future business model, open innovation and, in particular the collaboration with startups, is recognized as a means to keep the leading position in a changing industry. In this respect, utilities deriving from the European market, which is considered as a reference case for many other regions in the world, follow the 4th wave of Corporate Venture Capital (CVC) by initiating relevant programs.The aim of the paper is to examine the state of CVC programs of the European electric utilities and, more broadly, to examine their motives, to identify trends and strategies and to discuss the associated challenges. As our current knowledge on the subject is limited, the purpose of the study is to investigate this evolving phenomenon. To this end, a multiple case-study methodology is used by examining the CVC programs of four major European utilities (E.ON, EDF, Enel and Iberdrola). Findings suggest that CVC programs are now integrated in an Open Innovation approach and thus complemented by numerous other initiatives. All CVCs conduct investments tightly linked to the parent’s firm operations and the majority of them have more of a strategic (than financial) rationale in their investments. As a result, the cooperation between startups and the parent company is of great importance and poses a number of challenges related to the development of initiatives that would create linkages, achieve the alignment of the time frame and set up mutually beneficial commercial collaborations, including the ‘if’ and ‘how’ startups may work with competitors.